2020
DOI: 10.3390/agriculture10060211
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed Oil in New Application: Assessment of Structure of Oleogels Based on their Physicochemical Properties and Microscopic Observations

Abstract: The aim of the study was to analyze the effect of the type of gelling substance on the selected physicochemical properties of oleogels. Rapeseed oil (RO) and 5% w/w of one of the following structuring compounds (SC) were used for their production waxes: sunflower (SUN), candelilla (CAN), bees white (BW), bees yellow (BY), or monoacylglycerols (MAG). The ability of SC to form a network in RO was assessed on the basis of an analysis of the texture of oleogels (hardness and spreadability test, stability determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 40 publications
3
41
1
Order By: Relevance
“…The oil binding capacity of oleogels was determined by centrifugation as described in [5], using a CM-50 centrifuge SIA "ELMI" (Latvia). In a centrifuge tube, previously weighed, were placed approximately 1 g of oleogel and weighed again.…”
Section: Oil Binding Capacity (Obc)mentioning
confidence: 99%
“…The oil binding capacity of oleogels was determined by centrifugation as described in [5], using a CM-50 centrifuge SIA "ELMI" (Latvia). In a centrifuge tube, previously weighed, were placed approximately 1 g of oleogel and weighed again.…”
Section: Oil Binding Capacity (Obc)mentioning
confidence: 99%
“…For instance, rice bran wax in rice bran oil crystallizes as large dendritic crystals and the resulting network is loose and incapable of retaining the liquid oil inside it, but it also forms a fibrous morphology in other oils [42], while beeswax presented the same crystal arrangement and morphology when dispersed into medium chain triglycerides and long chain triglycerides [36]. In the study of rape seed oil oleogels, it was concluded that the more esters there are in the composition of a wax, the more needle-like a form (Figure 3) will result in the networks of structured oils; on the other hand, fat clusters irregularly distributed were observed for rape seed oil oleogel based on monoacylglycerols [66].…”
Section: Characterization Of the Oleogels Microstructurementioning
confidence: 97%
“…The microstructure of oleogels at 600× magnification, obtained by polarization (images at the top-1) and bright field (images at the bottom-2) for rapeseed oil oleogel structured with 5% sunflower wax (SUN), candelilla wax (CAN), bees wax white (BW), bees wax yellow (BY), or monoacylglycerols (MAG). Taken from Kupiec et al [66]. Copyright 2020 Creative Common Attribution License.…”
Section: Characterization Of the Oleogels Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…LMWOGs are often amphiphilic and self-assemble into supramolecular structures, building space-spanning networks [9]. Examples of LMWOGs that have been shown to form oleogels are monoglycerides [10][11][12][13][14][15][16][17][18], natural waxes [17,[19][20][21][22][23], enzymatically synthesized wax esters [24], ceramides [25], hydroxylated fatty acids [26,27], lecithin [28,29], and oligopeptides [30]. Additionally, combinations of LMWOGs have been studied, such as fatty acids and fatty alcohols [31,32], oleic acid and sodium oleate [33], sorbitan tri-stearate, tocopherol, phytosterol, β-citosterol or ceramide in combination with lecithin [34][35][36][37][38], γ-oryzanol and β-sitosterol [39][40][41][42][43], monoglycerides and phytosterols [44], beeswax and β-carotene [45], wax and monoglycerides [46], and combinations of fully hydrogenated oil, candedilla wax and monoglycerides [47].…”
Section: Introductionmentioning
confidence: 99%